Radial metallicity gradients with Galactic nebular probes. Issue Volume 14:Issue A30(2018) (August 2018) - García-Rojas, Jorge
Abstract: The study of radial metallicity gradients in the disc of the Milky Way is a powerful tool to understand the mechamisms that have been acting in the formation and evolution of the Galactic disc. In this proceeding, I will put the eye on some problems that should be carefully addressed to obtain precise determinations of the metallicity gradients.